EKONOMI HIJAU DAN KEADILAN SOSIAL: MENJEMBATANI KESENJANGAN MELALUI KEBERLANJUTAN - Hamka Hamka (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2025)
This study explores the relationship between green economy and social justice, as well as how these two concepts can be integrated to achieve inclusive sustainable development. In the face of global challenges such as climate change and economic inequality, green economy has emerged as a promising approach for environmentally friendly economic growth. However, its implementation often neglects social justice aspects, creating new gaps or exacerbating existing ones. This study analyses strategies and policies that can bridge the gap between environmental and social objectives, with a focus on green job creation, skills development, and fair distribution of benefits from economic transition. The findings indicate that effective integration between green economy and social justice requires a multidimensional approach involving various stakeholders. Key recommendations include: (1) developing a comprehensive policy framework that aligns environmental goals with social justice, (2) investing in education and training to prepare the workforce for the green economy, (3) strengthening mechanisms for public participation in decision-making related to environmental and economic policies, and (4) developing adaptive social protection systems that respond to structural economic changes. This study contributes to a deeper understanding of how sustainability can be achieved without sacrificing social justice, providing a foundation for further research and policy development in this area.